Action inflexibility and compulsive-like behavior accompany neurobiological alterations in the anterior orbitofrontal cortex and associated striatal nuclei - Laura M. Butkovich; Sophie T. Yount; Aylet T. Allen; Esther H. Seo; Andrew M. Swanson; Shannon L. Gourley (Scientific Reports)
Abstract The orbitofrontal cortex (OFC) is a large cortical structure, expansive across anterior-posterior axes. It is essential for flexibly updating learned behaviors, and paradoxically, also implicated in inflexible and compulsive-like behaviors. Here, we investigated mice bred to display inflexible reward-seeking behaviors that are insensitive to action consequences. We found that these mice also demonstrate insensitivity to Pavlovian-to-instrumental transfer, as well as compulsive-like grooming behavior that is ameliorated by fluoxetine and inhibitory, but not excitatory, chemogenetic modulation of excitatory OFC neurons. Thus, these mice offer the opportunity to identify neurobiological factors associated with inflexible and compulsive-like behavior. Experimentally bred mice suffer excitatory dendritic spine attrition, as well as changes in inhibitory synapse-associated proteins, GAD67/GAD1 and SLITRK3, largely in the anterior and not posterior OFC (or medial frontal cortex). They also display higher levels of the excitatory synaptic marker striatin in the nucleus accumbens and lower levels of the excitatory synaptic marker SAPAP3 in the dorsal striatum, striatal nuclei that receive input from the anterior OFC. Together, our findings point to the anterior OFC as a potential locus controlling action flexibility and compulsive-like behavior alike.